Viscosity Ratio and Interfacial Tension as Carbon Nanotubes Distributing Factors in Melt‐Mixed Blends of Polyamide 12 and High‐Density Polyethylene. Issue 4 (16th April 2014) - Zonder, L.; Mccarthy, S.; Rios, F.; Ophir, A.; Kenig, S.
ABSTRACT Polyamide 12 (PA12)/high‐density polyethylene (PE)/carbon nanotubes (CNTs) composites were prepared by three melt mixing sequences; premixing the CNT in the PA phase, premixing the CNT in the PE phase, and simultaneous mixing of all components. The interfacial tension and viscosity ratio between the components were altered by modifying the PE minor phase with PE‐graft‐maleic anhydride (PE‐g‐MAH) and by using different melt flow rate PE minor phase. Scanning electron microscopy (SEM) and volume resistivity (VR) measurements show that when the matrix's viscosity is greater than that of the dispersed phase, simultaneous mixing and premixing the CNT in the PE phase form a unique microstructure that yields a VR that is 4–6 decades lower than when premixing the CNT in the PA phase. When the viscosity of the dispersed PE phase is greater, kinetic restrictions limit the migration of the CNTs from the PE phase, resulting in high VR values for all mixing procedures. The wetting parameter was used to calculate the thermodynamic drive of the CNTs localization. It was found that the MAH modification reduces the interfacial tension between the CNT and the modified PE phase, which results in selective localization of CNT in there rather than in the PA phase. This observation was confirmed in SEM imaging and also expressed in high VR values of these composites.